Solving unknown primary cancer with earlier diagnosis - the SUPER-ED trial: study protocol for a stepped-wedge cluster randomised controlled trial to support earlier diagnosis for people presenting with malignancy of undefined primary origin - Anna Ugalde; Richard W. Tothill; Stephen Quinn; Hui-Li Wong; Owen Prall; Catherine Mitchell; Nilmini Wickramasinghe; Clare Fedele; Natalie Richards; Elizabeth Todio; Cindy Bryant; Louisa G. Collins; et al. (BMC Cancer)
Abstract Background People with malignancy of undefined primary origin (MUO) have a poor prognosis and may undergo a protracted diagnostic workup causing patient distress and high cancer related costs. Not having a primary diagnosis limits timely site-specific treatment and access to precision medicine. There is a need to improve the diagnostic process, and healthcare delivery and support for these patients. This trial aims to implement and evaluate an optimal model of care for people presenting with MUO to reduce time to diagnosis, improve patient experiences and reduce healthcare costs. Methods/design This is a pragmatic stepped-wedge cluster randomised trial comparing a control phase of standard practice with an intervention phase. Patient inclusion criteria are: 1) age 18 years or older, 2) presenting with suspected metastatic malignancy without an obvious primary site on imaging, 3) clinically appropriate to undergo diagnostic work-up and 4) able to provide written or verbal consent. The intervention is a new model of care comprising four key components: standardised diagnostic workup, dedicated cancer care coordinators, virtual multidisciplinary meetings and a website resource for patients, carers and clinicians. The primary endpoint is the time to completion of minimum diagnostic workup. Secondary outcomes are whether the type of tumour is diagnosed, clinical trial participation, referral to palliative care, patient-reported physical, social and mental health, patient-reported understanding and uncertainty. Implementation outcomes include acceptability, feasibility, fidelity and adoption and health care use and costs. Intervention implementation will be supported using clinical leadership, education and reinforcement. Patients who consent to having their data collected will receive the model of care active at the site at the time of recruitment. Patients will complete a patient-reported outcomes questionnaire four months after study enrolment. A health economic analysis will be included. Across 15 hospitals, a total sample size of 240 is planned. Discussion There is a lack of intervention research for people presenting with MUO. The stepped-wedge design seeks to mitigate the potential challenge of enrolling people with a poor prognosis and high symptom burden in trials. This research will generate important evidence with scalability for future research at trial completion. Trial registration ACTRN12622001504707